KEJELASAN SASARAN ANGGARAN DAN SPIP TERHADAP AKUNTANBILITAS KINERJA INSTANSI DIMODERASI PARTISIPASI PENYUSUN - Mardiana, Mardiana; Setiyowati, Supami Wahyu (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study was to examine and explain the clarity of budget targets, and the internal control system on performance accountability in OPD Malang City in moderation of budgetary participation. This study uses quantitative research methods. Population of 34 Regional Apparatus Organizations in Malang City. The data analysis technique used multiple regression analysis. The results showed the clarity of budget targets, and the internal control system had an effect on performance accountability in OPD Malang City. A clear budget and according to organizational goals increases the accountability of the performance of government agencies. The implementation of an internal control system in each activity increases the accountability of the performance of government agencies. Participation in budgeting moderates the relationship between the clarity of budget targets and the internal control system that affects performance accountability. Participation in budgeting is very important for the preparation of a government budget in accordance with organizational goals. With participation in budgeting, the clarity of budget targets and the internal control system has increased and has an impact on increasing the accountability of government performance.